ANATOMICAL COMPARATIVE FOR TWO SPECIES AMARANTHUS ALBUS L. AND AMARANTHUS GRACILIS DEFS AMARANTHACEAE) IN IRAQ.) - S. Nameer,; S.A.Aliwy,; L. K. A. Al-Azerg,; H. Redah, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study delts with anatomical characters for the vegetative parts of two species of the family Amaranthaceae in Iraq, Amaranthus albus L. and A.gracilis Defs, as it presents results and characters had been study for the first time in Iraq .The study included epidermis and stomatal complex, the results show that the first species have Anomocytic and Anisocytic type While the other species have Anomocytic and Tetracytic type of stomatal complex,Venation of leaves had been studied also, study included the longitudinal sections of leaves and vertical sections for stems, petioles and roots. Longitudinal sections leaf of Amaranthus gracilis recognized by presence of sandy crystals, Cross sections of petioles show that the first species have crescent shaped quadric-side, while the other one have crescent shape but winged-side, The cross section of stem and roots of Amaranthus gracilis have anomalous growth phenomenon. It could be depended to studied traits in isolation identification and classification of different plants species.